Implementation of Multi-Attribute Utility Theory Method for Selecting Social Assistance Recipients - Wahyu Widodo; irsyad Panca Gunawan (Fakultas Teknik Universitas Bhayangkara, 2023)
Amil Zakat Infaq and Shadaqah Muhammadiyah Institution (LazisMu) Ayah is one of the national amil zakat institutions located in Ayah District, Kebumen Regency. Every month, LazisMu Ayah Service Office provides assistance to people in need in the form of house renovation programs, scholarships for high school or college level education, and business capital. The problem that is often encountered in determining potential aid recipients is that the large number of requests for aid is disproportionate to the number of officers processing the screening data. Apart from that, the selection process for aid recipients still uses manual methods, so it often causes problems such as the selection process for selecting aid candidates taking up to a week and miscalculations occurring, resulting in inaccurate results in the selection of potential aid recipients. Therefore, the method used as a solution model in providing decisions on the system for selecting potential aid recipients at LazisMu Ayah is a decision support system using the multi-attribute utility theory (MAUT) method. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case, the intended alternative is people who are entitled to receive assistance based on 10 criteria. The results of the black box testing show that the system created is in accordance with the design and can be used as a tool. making decisions on determining aid recipients, so that LazisMu Ayah services can be improved because the selection process becomes faster, more accurate, and on target.